99mTc-rituximab tracer injection for guiding internal mammary sentinel lymph nodes biopsy in primary breast cancer: A prospective observational study - Chen, Wenxin; Su, Yaodong; Zhang, Hui; Zhang, Yu; Zhu, Lin; Lin, Mengbo; Lin, Zhiyi; Yu, Mingdian; Yang, Shengping; Zhang, Yanmin (Frontiers in Oncology, 2023)
Objective: To explore the use of 99mTc-rituximab tracer injection for internal mammary sentinel lymph node (IM-SLN) detection in patients with primary breast cancer. Methods: This prospective observational study enrolled female patients with primary breast cancer between September 2017 and June 2022 at Fujian Provincial Hospital. The participants were divided into the peritumoral group (two subcutaneous injection points on the surface of the tumor), two-site group (injections into the glands at 6 and 12 o’clock around the areola area), and four-site group (injections into the gland at 3, 6, 9, and 12 o’clock around the areola area). The outcomes were the detection rates of the IM-SLNs and axillary sentinel lymph nodes (A-SLNs). Results: Finally, 133 patients were enrolled, including 53 in the peritumoral group, 60 in the two-site group, and 20 in the four-site group. The detection rate of the IM-SLNs in the peritumoral group (9.4% [5/53]) was significantly lower than in the two-site (61.7% [37/60], P<0.001) and four-site (50.0% [10/20], P<0.001) groups. The detection rates of A-SLNs among the three groups were comparable (P=0.436). Conclusion: The two-site or four-site intra-gland injection of 99mTc-rituximab tracer might achieve a higher detection rate of IM-SLNs and a comparable detection rate of A-SLNs compared with the peritumoral method. The location of the primary focus has no impact on the detection rate of the IM-SLNs.